CULTURA POLÍTICA Y DEMOCRATIZACIÓN EN AMÉRICA LATINA - Heras Gómez, Leticia (2023)
The purpose of this paper is to illuminate how the enduring political values inherited from the colonial epoch have had a long duree in Latin American countries, and the consequences for the installation of democratic regimes, throughout the 19th up to the end of the 20th century. The central argument is that democracy is not only about economic welfare or competitive political system, but is about how democratic values are developed in societies where, due to their heavy non-democratic historical inheritance, those ones hardly begin to root. In order to achieve this goal we combine a historical qualitative approach and a quantitative method using public opinion information.